The Effect of Different Lactic Acid Bacteria Inoculants on Silage Quality, Phenolic Acid Profiles, Bacterial Community and In Vitro Rumen Fermentation Characteristic of Whole Corn Silage - Yan-Lu Wang; Wei-Kang Wang; Qi-Chao Wu; Fan Zhang; Wen-Juan Li; Zhuo-Meng Yang; Yu-Kun Bo; Hong-Jian Yang (Fermentation, 2022)
Corn silage is an important source of forage, but whether or not bacterial inoculants should be applied is somewhat controversial in ruminant feeding practice. In the present study, chopped whole corn plants treated with a single inoculant of Lactobacillus buchneri (LB), Lactobacillus plantarum (LP), Pediococcus pentosaceus (PP) served as either homofermentation (e.g., lactate only) or heterofermentation (e.g., lactate and acetate) controls and compared with those treated with either a mixture of the lactic acid bacteria (QA: 60% LP, 10%PP, 30% LB) or a mixture of the lactic acid bacteria (QB: 60% LP, 15% PP, 25% LB), to investigate their effects on the fermentation quality, ester-linked phenolic acids, and in vitro digestibility. After 60 day ensiling, the addition of QA exhibited the lowest pH (3.51) with greater lactic acid (LA) production. The ester-linked ferulic acid (FAest) and p-coumaric acid (pCAest) concentrations were significantly decreased during 60 days ensiling. And among all these groups, the LB and QA treated group showed a lower concentration of FAest and pCAest than other groups. After 60 days ensiling, Lactobacillus was the dominant genus in all LAB treated groups. Meanwhile, negative correlations of Bacillus, Bacteroides, Bifidobacterium, Blautia, Prevotella, Ruminococcus, and Roseburia with FAest content after 60 days ensiling occurred in the present study. Komagataeibacter was mainly found in LB and PP addition silages, and presented a significant negative effect with the level of acid detergent fiber (ADF). To explore whether the addition of LABs can improve digestibility of whole corn silage, an in vitro rumen fermentation was conducted using the 60 day ensiled whole corn silages as substrates. The QA addition group exhibited a greater 48 h and 96 h in vitro dry matter and ADF disappearance, greater 48 h gas production and less methane emissions. Even though there were the same neutral NDF levels in corn silages treated with LB and QA after 60 days ensiling, the QA treated silages with lower FAest and pCAest presented higher IVDMD after 96 h and 48 h in vitro fermentation. In brief, the addition of mixed inoculants of 60% LB,10% PP, 30% LB compared with the addition of whichever single HoLAB or HeLAB inoculants, facilitated the release of ester-linked phenolic acids (e.g., ferulic and p-coumaric acids) and remarkably, improved silage quality in terms of sharp pH decline and greater lactate production. Taken together with the improvement in rumen microbial fermentation, the results obtained in the present study provided concrete evidence for the role of mixed LAB application in corn silage preparation for ruminant feeding practices.